2013
DOI: 10.3390/toxins5020267
|View full text |Cite
|
Sign up to set email alerts
|

Is Protein Phosphatase Inhibition Responsible for the Toxic Effects of Okadaic Acid in Animals?

Abstract: Okadaic acid (OA) and its derivatives, which are produced by dinoflagellates of the genera Prorocentrum and Dinophysis, are responsible for diarrhetic shellfish poisoning in humans. In laboratory animals, these toxins cause epithelial damage and fluid accumulation in the gastrointestinal tract, and at high doses, they cause death. These substances have also been shown to be tumour promoters, and when injected into the brains of rodents, OA induces neuronal damage reminiscent of that seen in Alzheimer’s disease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
68
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(68 citation statements)
references
References 133 publications
(198 reference statements)
0
68
0
Order By: Relevance
“…The viability of the differentiated intestinal Caco-2 cells was not impaired by the concentrations of OA tested. OA was previously reported to induce several cytoskeleton alterations in different cell systems that could be due to different mechanisms that involve disruption of F-actin and that stimulate tight junction disassembly leading to diarrhea in vivo (Munday, 2013;Vale and Botana, 2008;Vilarino et al, 2008). We found a dose and time dependent reduction of TEER values on these Caco-2 monolayers exposed to OA indicating tight-junctions alterations.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…The viability of the differentiated intestinal Caco-2 cells was not impaired by the concentrations of OA tested. OA was previously reported to induce several cytoskeleton alterations in different cell systems that could be due to different mechanisms that involve disruption of F-actin and that stimulate tight junction disassembly leading to diarrhea in vivo (Munday, 2013;Vale and Botana, 2008;Vilarino et al, 2008). We found a dose and time dependent reduction of TEER values on these Caco-2 monolayers exposed to OA indicating tight-junctions alterations.…”
Section: Discussionmentioning
confidence: 58%
“…There is some controversy about this phosphatase inhibition being the only responsible for the toxic effects of OA and its analogs and recent papers have suggested that it should be re-evaluated (Espina et al, 2009;Louzao et al, 2005Louzao et al, , 2003Munday, 2013;Vilarino et al, 2008;Wang et al, 2012), especially when focusing on the exact triggering mechanism of the diarrheic effects (Munday, 2013). In this sense, methyl okadaate and OA disrupt the F-actin cytoskeleton in hepatocytes and in neuroblastoma cells even though this OA analog has little or no effect on the activities of PP2A and PP1 (Espina et al, 2009;Louzao et al, 2005Louzao et al, , 2003Vilarino et al, 2008).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…TEM analysis revealed that neither OA nor DTX1 changed tight junctions, therefore fluid accumulation in the intestine and diarrhea could not be related to increase in paracellular permeability along with tight junctions disruption as was previously suggested [11]. Intestine of mice administered with the highest dose of each toxin presented decreased enterocytes microvilli that were not seen after oral DTX2 administration [29].…”
Section: Cellular Physiology and Biochemistrymentioning
confidence: 76%
“…It was previously suggested that PPs inhibition was responsible for the diarrheic effect of OA and derivatives [8]. However, other actions not related to PP inhibition [9,10], have been reported suggesting that the mechanism of toxicity of these compounds must be re-evaluated [11].…”
Section: Introductionmentioning
confidence: 99%